2015
DOI: 10.1021/ac503933t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Speciated Isotope Dilution Mass Spectrometric Methods for Accurate, Reproducible and Direct Quantification of Reduced, Oxidized and Total Glutathione in Biological Samples

Abstract: Novel protocols were developed to accurately quantify reduced (GSH), oxidized (GSSG) and total (tGSH) glutathione in biological samples using molecular speciated isotope dilution mass spectrometry (SIDMS). For GSH and GSSG measurement, the sample was spiked with isotopically enriched analogues of the analytes ((310)GSH and (616)GSSG), along with N-ethylmaleimide (NEM), and treated with acetonitrile to solubilize the endogenous analytes via protein precipitation and equilibrate them with the spikes. The superna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…Then samples are analyzed by tandem mass spectrometry (NEM was used as masking agent and added to collecting tubes) and the analytes are quantified using the stable-isotope labelled analogs. Oxidation of GSH to GSSG was corrected by using mathematical relationships in double-spiking SIDMS [44]. These LC-MS/MS methods may represent a good alternative to spectrophotometric and HPLC with UV absorbance detection assays but a good agreement with these techniques still lacks.…”
Section: Suggested Methods To Measure Gsh and Gssgmentioning
confidence: 99%
See 2 more Smart Citations
“…Then samples are analyzed by tandem mass spectrometry (NEM was used as masking agent and added to collecting tubes) and the analytes are quantified using the stable-isotope labelled analogs. Oxidation of GSH to GSSG was corrected by using mathematical relationships in double-spiking SIDMS [44]. These LC-MS/MS methods may represent a good alternative to spectrophotometric and HPLC with UV absorbance detection assays but a good agreement with these techniques still lacks.…”
Section: Suggested Methods To Measure Gsh and Gssgmentioning
confidence: 99%
“…In whole blood of 9 subjects, Fahrenholz et al reported 1.46±0.07 μmol/g for GSH and 2.4±0.4 nmol/g for GSSG, yielding a mean GSH/GSSG ratio of 608. In RBCs of 9 healthy children, this group reported 1.69±0.83 μmol/g for GSH and 6.1±3.8 nmol/g GSSG, corresponding to a mean GSH/GSSG ratio of 277 [44]. These data indicate considerable discrepancies even between highly sophisticated LC-MS/MS methods and point out to additional not yet fully recognized pre-analytical and/or analytical problems.…”
Section: Suggested Methods To Measure Gsh and Gssgmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed reviews have been published elsewhere (Monostori et al, 2009; Iwasaki et al, 2009). The most popular of these techniques make use of high-performance liquid chromatography (HPLC) separation with UV absorbance (Reed et al, 1980; Katrusiak et al, 2001; Bald and Glowacki, 2005), chemiluminescence (McDermott et al, 2011a,b), fluorescence (Imai et al, 1983; Martin and White, 1991; Paroni et al, 1995; Yang et al, 1995; Kand’ar et al, 2007), electrochemical (Rodriguez-Ariza et al, 1994; Rose and Bode, 1995; Lakritz et al, 1997; Potesil et al, 2005; Sequellerio et al 2012), or mass spectrometry-based (Lafaye et al, 2005; Bouligard et al, 2006; Iwasaki et al, 2009; Squellerio et al, 2012; Moore et al, 2013; Zhang et al, 2015; Fahrenholz et al, 2015) detection. Even nanosensors for GSH and GSSG are now being developed (Xu et al, 2012; Moore et al, 2013; Ni et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…So ist es einem Autor zufolge “erwiesen, dass die gemessenen Konzentrationen … zwischen verschiedenen Arbeitsgruppen stark abweichen. … Ergebnisse sollten erneut auswertet werden, sobald (es) eine allgemeine Einigung über die physiologischen Konzentrationen (gibt) …” [52] Diese Unstimmigkeit wurde der Variabilität der Analysemethoden, der Verwendung unterschiedlicher Matrizen (Plasma oder Blut), der Oxidation von Probenmaterial, inkonsistenten Aufbereitungsmethoden der Proben und allgemein dem Mangel an standardisierten Methoden zugeschrieben . Die Handhabung der Proben wurde als Hauptursache für die fehlende Reproduzierbarkeit und hohe Varianz in den GSH‐Bestimmungen beschrieben .…”
Section: Wichtige Fragestellungen In Bezug Auf Thiolsondenunclassified